2017
DOI: 10.3390/en10040430
|View full text |Cite
|
Sign up to set email alerts
|

Financial Appraisal of Small Hydro-Power Considering the Cradle-to-Grave Environmental Cost: A Case from Greece

Abstract: Abstract:In the last decades increasing attention to environmental issues has come to the fore due to the looming issue of climate change. The growing demand for energy, coupled with the increasing greenhouse gas (GHG) emissions, have forced the study and development of energy plants that use renewable energy sources (RES), as electricity generation is one of the major contributors to anthropogenic emissions. Small hydropower plants are of particular interest as their potential is assumed to be high. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…There are non-renewable sources of electricity, which will likely be exhausted at a certain time, among them are the natural gas, oil and hard coal. At the same time, generating electricity from renewable sources is considered an attractive option for the environment [2]. Renewable energies or renewable sources are gaining prominence worldwide and providing clean electricity to the population through technological developments.…”
Section: Generation Of Electricity In the Global Scenariomentioning
confidence: 99%
“…There are non-renewable sources of electricity, which will likely be exhausted at a certain time, among them are the natural gas, oil and hard coal. At the same time, generating electricity from renewable sources is considered an attractive option for the environment [2]. Renewable energies or renewable sources are gaining prominence worldwide and providing clean electricity to the population through technological developments.…”
Section: Generation Of Electricity In the Global Scenariomentioning
confidence: 99%
“…Furthermore, wave power development is perspective and feasible for several Russian Federation regions (e.g., the Black Sea coast, Russia's Far East coast, Russian Arctic shelve), EU countries [6][7][8] and other parts of the world [9][10][11][12]. Research results and international experience of using wave power plants show [13][14][15] that it is practical to revamp, design and build coast-protecting structures with additional modifications in the form of wave power plants.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Alexandros et al [8], it was found that the potential of small hydropower (1-10 MW in this context) in Sub-Saharan Africa is estimated at 21,800 MW and run-ofriver hydropower plants are generally categorized as small hydropower plants [9][10][11][12][13]. Additionally, more particularly in Cameroon, the small hydropower capacity is estimated at 970 MW, according to the UNIDO small hydropower development report [14].…”
Section: Introductionmentioning
confidence: 99%